Monitoring and Evaluation Strategy School Internal Quality Assurance System - Endang Pujiarti; Faisal R. Dongoran; Ratna Sari; Friska Deliana Purba; Kartika Dewi Ahmadi; Sri Mulya (UMSU, 2023)
Strategy for Monitoring and Evaluation (Monev) of the School Internal Quality Assurance System, 2022. This article aims to find out the strategies that must be carried out in monitoring and evaluation activities in the school's internal quality assurance system. Monitoring and Evaluation has objectives in terms of the interests of decision making, systematic data collection, and program improvement. The monitoring and evaluation approaches used are social system reporting (social experimentation), social auditing and material collection (social accounting), social experimentation for social research (social research cumulation). While the monitoring and evaluation technique carried out is by observation technique, namely by making direct visits to the activity site. The monitoring process is carried out with the planning stage, namely by identifying the things to be monitored, the implementation stage by measuring the teacher's skills in using teaching methods, and the reporting stage, by determining whether work performance meets predetermined standards.